Strategies for building edible green infrastructure in traditional villages and insights into bio-districts: a case study of Dong villages in Huanggang, China - Zi, Chengxiang; Winterbottom, Daniel; Liu, Juanjuan (Frontiers in Sustainable Food Systems, 2024)
As a concept that emerged in Europe, a bio-district is an area where different actors work together for the innovative and integrated transformation of rural food systems and the sustainable management of local resources, based on the principles of organic farming and with farmers playing a central role. Traditional Chinese villages represent sustainable models for the management of rural food systems and natural resources, developed by indigenous peoples who have been in “dialogue” with the land over millennia and adapted to specific geographical and ecological environments. These models encompass well-established Edible Green Infrastructure (EGI) ecological structures, rich in indigenous knowledge and understanding of the environment that support food supply and regional ecological sustainability. Our case study focuses on a well-preserved village of the Dong ethnic group in southwest China, which maintains traditional livelihoods and a local food system. We used field surveys, interviews, participatory mapping to propose an EGI model of the traditional Dong village, which comprises the following key elements: the “rice-fish-duck” cycle as a key factor of traditional livelihoods, the hierarchical ecological structure of “households-groups-village”, and corresponding management models. This study aims to comprehensively understand the knowledge of sustainable food systems and natural resource management derived from traditional China. It achieves this by theoretically analyzing the Traditional Village Edible Green Infrastructure (EGI) that has evolved over China’s thousand-year agricultural civilization. The objective is to apply this understanding to the construction of bio-districts in rural China. EGI model in traditional villages worldwide have the potential to offer lessons from millennium-old indigenous agricultural systems, which may have relevance for current environmental and food crises faced by our industrialized world, the construction of bio-districts and organic regions, and the sustainable management of local resources.